Pengaruh Hybrid Working Terhadap Loyalitas Karyawan Generasi Z Di Industri Kreatif - Syahrinda Fina; Wasiman (Prosiding, 2025)
Since the outbreak of Covid-19, many countries have decided to adopt strict health regulations and implement working from home as part of the telecommuting scheme. In the midst of the pandemic, the working world underwent a significant transformation. Flexibility and balance between work and personal life became a top priority, especially for Generation Z employees. Generation Z has entered productive age and started joining the workforce. The digital technology environment that accompanies their growth makes Gen Z have various advantages. However, this generation also faces new challenges. Gen Z frequently switches workplaces even within months. At the same time, hybrid working emerged as a work model considered to provide comfort. The lack of social interaction and direct collaboration in this system poses challenges because it can lead to decreased team harmony. The implementation of hybrid working requires greater attention from companies to maintain Generation Z’s loyalty. If companies are unable to adjust their work systems to the need for flexibility and psychological support, they are likely to lose young potential talents. The world of work is now required to adapt to the expectations and characteristics of the new workforce, especially Generation Z, who are starting to dominate the labor market. Failure to adjust the work environment to their preferences can result in a high turnover rate.